Comparative evaluation of rheological characteristics of giomers and other nano-flowable resin composites in vitro - Loulwa M. Al-Saud (Medical Journals Sweden, 2021)
Objective The purpose of this research was to determine the viscoelastic properties of a group of commercially available nano-flowable resin composites; and to explore the relation between these properties and the materials' composition (with/without fluoride), filler size description (nano-filled, nanohybrid and submicron-filled) and filler loading (by volume). Methods Rheological measurements were performed using a rheometer. A Dynamic frequency sweep test was conducted to evaluate the complex viscosity, storage and loss moduli, loss tangent, and complex shear modulus at an angular frequency (ω) of 0.1-100 rad/s. Comparative evaluations of the nano flowable resin composites on rheological properties was performed, and statistically analyzed using one-way ANOVA. Results The results indicated that all the tested materials exhibited shear-thinning flow behaviour. As the shear rate increased, the complex viscosity of the nano-flowable composites decreased. The nanohybrid filled flowable resin composites exhibited the highest complex viscosity, while the nano-filled flowable resin composites exhibited the lowest value. The submicron-filled materials exhibited the lowest complex shear moduli and loss tangent values. Conclusions: The findings from the current study provided comprehensive evaluation of the rheological properties of different nano-flowable composites. The observed differences in rheological properties among the tested materials were independent of their fluoride content or filler size. Furthermore, no relationship was found between the complex viscosity of the tested nano-flowable resin composites and their filler volume.